Ability of Allium cepa L. root tips and Tradescantia pallida var. purpurea in N-nitrosodiethylamine genotoxicity and mutagenicity evaluation - Claudia R. de Rainho; Andréa Kaezer; Claudia A.F. Aiub; Israel Felzenszwalb (Anais da Academia Brasileira de Ciências, 2010)
N-nitroso compounds, such as N-nitrosodiethylamine (NDEA), can be formed by the reaction of secundary amines with nitrosating agents, and are suspected to be involved in tumors in humans. NDEA has been considered a weak carcinogen in genotoxic assays probably due to the inefficient nitrosamine activation system that is used and/or to the efficient repair system. In this work, we evaluated the sensibility of Allium cepa L. root tips and Tradescantia stamen hair mutation assay (Trad-SH) using Tradescantia pallida var. purpurea for NDEA (0.1; 0.5; 5 and 25mM) genotoxicity and mutagenicity induction. Allium cepa L. was treated with different NDEA concentrations for 3h, for 3 consecutive days, including negative control (distilled water) and positive control maleic hydrazide (MH 30mg/mL). After treatment, the roots were hydrolyzed, squashed, and the mitotic index (MI) and cytological abnormalities were scored. The results revealed a cytostatic effect of NDEA (0.5 and 5mM), showing a significant reduction in the MI. Chromosome stickiness suggests a NDEA toxic effect. T. pallida purpurea did not respond to mutagens with a dose-dependent pattern. In conclusion, our study indicates that the root tips of Allium cepa L. have sensibility to detect NDEA genotoxicity, but not for Trad-SH test. Nitrocompostos, como N-nitrosodietilamina (NDEA), podem ser formados pela reação entre uma amina secundária e agentes nitrosantes e são suspeitos de estarem envolvidos na formação de tumores em humanos. NDEA é considerada um carcinógeno fraco e ensaios genotóxicos provavelente pela utilização de um sistema de ativação ineficiente e/ou pela utilização de um eficiente sistema de reparo. Neste trabalho, nós avaliamos a sensibilidade de ensaios com Alliu cepa L. e Tradescantia pallida var. purpurea (Trad-SH) à genotoxicidade e mutagenicidade induzidas por diferentes concentrações de NDEA (0,1; 0,5; 5 e 25mM) por 3h, por 3 dias consecutivos, incluindo controle negativo (água destilada) e controle positivo, hidrazida maleica (MH 30mg/mL). Depois do tratamento, as raízes foram hidrolizadas, esmagadas e o índice mitótico (IM) e anormalidades citológicas foram contadas. Os resultados revelaram um efeito citostático de NDEA (0,5 e 5mM), pela significante redução do IM. Chromosome stickiness sugere um efeito citotóxico de NDEA. T pallida purpurea não respondeu ao mutágeno com um padrão dose dependente. Em conclusão, nossos estudos indicaram que raízes de Allium cepa L. possue sensibilidade na detecção genotóxica de NDEA, mas não para o ensaio Trad-SH.